ANALISIS PEMBUATAN PIPA BAJA SISTEM DUA BAGIAN LAS ASTM A139 DENGAN MENGGUNAKAN METODA LSAW = MANUFACTUR ANALYSIS DUAL SEAM WELD STEEL PIPE ASTM A139 BY USING LSAW METHODE - Djoko W. Karmiadji; Gery Setiadi (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2014)
One of the main components of the manufacture of steel pipe is in the form of plate steel sheet, slab or hot roll coil, which of these materials may be made for various types of pipes, among others, seamless, Electric Wire Resistance, Spiral and Longitudinal pipes.The main material used welding steel pipe is a steel plate or hot roll coil. Material procurement dependence becomes an obstacle for welding steel pipe mill, which at this moment in our country's steel mills have not been able to produce material of diameter of 24